(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2022)
The study targets at farmer’s perception and their cognition how they conceive that agricultural performance has been affected and devastated through industrial work. It reviews and investigates the opinion of 25% farmers of two villages from each upazila of two named Madhapur and Habiganj sadar upazila in Sylhet division where Charu Ceramic Industry Limited and Olipur industry are located respectively from mid-September to mid-October, 2021 through survey of questionnaire, interview and group discussion. According to 85% farmers, the industry shades agriculture by imposing an adverse and toxic impact on agricultural exposure and development. Among them, (41.6% and 48.4%) of farmers realize that the industry creates high propensity of losing standard quality of soil and water, respectively. They (40.2%) notice that invasion of several dangerous insects on crops has become prominent and unmanageable near the industrial area. The study represents such kind of realization of farmers to show a salient feature in view of their finding causes and intuition with significant numerical data. Int. J. Agril. Res. Innov. Tech. 11(2): 133-138, Dec 2021